2008
DOI: 10.1063/1.2966714
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined deformation and heat treatment on the superconducting properties of a niobium-titanium alloy

Abstract: The influence of combined deformation, including equal-channel multiangle pressing (ECMAP), and heat treatment on the critical current density of a superconducting wire made from the alloy Nb+60at.% Ti is investigated. It is found that the combined deformation, including ECMAP, can increase the critical current density by up to two times. The relationship between the character of the structural inhomogeneities and the pinning force is estimated. The pinning efficiency is linked to the nanostructural state of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Gajda et al [18] showed for the first time that dislocations effectively increase J c in magnetic fields from 6 to 8 T in NbTi. There are several methods that allow us to obtain high-field pinning centers and more connections between the grains in superconducting wires, tapes, bulks, and thin layers, e.g., cold drawing (CD) [20,[24][25][26], equal-channel multi-angle pressing (ECMAP) [27,28], cold rolling (CR) [25,29], cold pressure (CP) [30], hot isostatic pressure (HIP) [25,31,32], and C doping [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Gajda et al [18] showed for the first time that dislocations effectively increase J c in magnetic fields from 6 to 8 T in NbTi. There are several methods that allow us to obtain high-field pinning centers and more connections between the grains in superconducting wires, tapes, bulks, and thin layers, e.g., cold drawing (CD) [20,[24][25][26], equal-channel multi-angle pressing (ECMAP) [27,28], cold rolling (CR) [25,29], cold pressure (CP) [30], hot isostatic pressure (HIP) [25,31,32], and C doping [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In [16], it was stated that the Cu-NbTi composite specimens prepared using ECMAP (e = 13.12) and without it have the second order microstresses 1.96 × 10 -3 and 1.96 × 10 -3 , respectively. It follows that the action of the first factor is doubtful.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the NbTi wires were treated with the two methods: traditional method and equal channel multi-angle pressing (ECMAP) [1]. The traditional method included hydroextrusion (HE) and the process of drawing.…”
Section: Samples Preparationmentioning
confidence: 99%
“…The degree of deformation was e = 0.82 per pass [1]. The samples were obtained in four various passes ECMAP: first, after 4 passes -e = 3.28, second after 8 passes e -6.56, third after 12 passes e -9.84, fourth after 16 passes e -13.12.…”
Section: Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation